HUBUNGAN PENGETAHUAN PASIEN TENTANG PENYAKIT GAGAL GINJAL KRONIS DENGAN KEPATUHAN DIET DI RUANG HEMODIALISIS RSUD LAWANG - Indah Lestari, Dian; Prawito, Ns.; Rustanti, Elly (LPPM STIKES HUSADA JOMBANG, 2023)
Chronic kidney disease is a disease where the body is not able to maintain metabolism and balance the fluid and electrolytes so which could increase the urea level in the blood. The number of patients with chronic kidney disease in Indonesiahas increased. The management of chronic kidney disease could be done in various ways, including diet, fluid restriction, drugs and renal replacement therapy. This study aims to determine the correlation of patient knowledge about chronic kidney disease with dietary compliance in the Hemodialysis room of RSUD Lawang. This study utilized a non-experimental method that is correlational analysis with a cross-sectional approach. The population of this research were patients with chronic kidney disease who routinely undergo hemodialysis at RSUD Lawang as many as 40 respondents. Data collection wa carried out on 25-30 July 2022 with interviews using a questionnaire and data analysis using the Spearman Rho statistical test. The results showed that almost all of them, namely as many as 34 respondents (85%) had good knowledged about chronic kidney disease and all respondents, namely 40 respondents (100%) were obedient to the chronic kidney disease diet. The test results obtained p-value = 0.000 (α<0.005), it can be concluded that there is a correlationship between patient knowledge about chronic kidney disease and dietary compliance in the Hemodialysis room of RSUD Lawang This research is expected to increase the knowledged and patient complaince in the Hemodialysis room of RSUD Lawang about the chronic kidney disease diet. For health workers, it is expected to further improve education so that patients become obedient to hemodialysis therapy and chronic kidney disease diet so that they can improve the patients quality of life.